Dynamic Electromagnetic Force of Stator Core for Hydro-generators under Phase to Phase Short Circuit with Two Fault Points Close to the Neutral Point - XIAO Shi-yong; WANG Yun-yang; GE Bao-jun (Journal of Harbin University of Science and Technology, 2021)
Aiming at the problem that the phase to phase short-circuit with two fault points close to the neutral point may cause dead region of protection schemes of large synchronous generators, and in order to prevent the further expansion of the fault from causing serious damage to generators, it is imperative to detect short-circuit faults under the dead zone of main protection scheme accurately and timely by merging electro-mechanical information.A external circuit-coupled finite element model of synchronous generators which can accurately simulate the short-circuit position is established. The fault current and air-gap magnetic field of a 300MW hydro-generator in a power station are calculated when the phase to phase short-circuit with two fault points are close to the neutral point occurs, and the dynamic electromagnetic force of the stator tooth is calculated by the Maxwell stress method. The location of maximum electromagnetic force at stator tooth is found under the fault condition. The local dynamic electromagnetic force changing with time and space distribution are revealed. The study in this paper provides the basis for the optimization design of the stator core and faults diagnosis method by merging electro-mechanical information.